Morbidity and Mortality Pattern of Newly Born Babies in a Teaching Hospital - Haider Shirazi ,Sadia Riaz ,Raja Amjad Mahmood (Journal of Rawalpindi Medical College, 2015)
Background: To determine the disease pattern and causes of neonatal mortality in a teaching hospital. Methods: In this prospective hospital based observational study all the new born babies admitted because of illness were enrolled . Data was collected on a predesigned proforma including information about weight, sex, gestational age, and mode of delivery. Neonatal information was collected at time of admission. A single most appropriate diagnosis was given by the senior physician. The inclusion criteria was all the neonates brought for admission to the neonatal unit.Diagnosis was mainly clinical and based upon the WHO criteria. Laboratory diagnostic tests and radiology were used to confirm the diagnosis. Primary disease was considered as final diagnosis even if the baby developed complications of primary disease or had more than one disease. Meconium aspiration syndrome was diagnosed on basis of history, clinical and radiological findings. Birth asphyxia was diagnosed clinically and APGAR score. Sepsis evaluation was based on clinical and laboratory indices like complete blood counts, C- reactive protein (CRP) and blood cultures collectively. Results: A total of 53395 babies were delivered during this period .Out of this only 5595 babies were admitted for treatment. Out of 5595 admitted sick neonates, 3024 (54%) were male and 2571 (46%) were female. Premature were 3260 (58%) and low birth weight were 2635(47%). Neonatal sepsis (25%), birth asphyxia (19%) and respiratory distress syndrome (19.4%) were the leading causes of morbidity. The rest was contributed by meconium aspiration syndrome (9.3%), neonatal jaundice (7.8%), congenital pneumonia (7.8%) and transient tachypnea of newborn (TTN) (4.7%). A total of 1074 babies died which is 2% of all deliveries and 19.2% of all admitted babies. The three major causes of mortality were RDS (30%), birth asphyxia (22.4%), sepsis (16.8%). Congenital pneumonia and MAS contributed 19% each. The case fatality for prematurity was 18% and for low birth weight 16%. Conclusion: Neonatal sepsis, birth asphyxia, prematurity and the low birth weight were the leading causes of neonatal mortality. Deaths due to severe respiratory distress syndrome (RDS) was high so interventions to reduce preterm delivery, low birth weight and birth asphyxia should be planned. Establishment of level II neonatal care units at tehsil and district levels will definitely reduce the neonatal deaths.